Trust Issues: Evidence from Second Generation Immigrants - Martin Ljunge (Research Institute of Industrial Economics (IFN), 2012)
This paper estimates the intergenerational transmission of trust by studying second generation immigrants in 29 European countries with ancestry in 87 nations. There is significant transmission of trust on the mothers side. The transmission is stronger in Northern Europe. Ancestry from more developed countries suggests a stronger transmission of trust, but the heterogeneity in ancestry dissipates for individuals who reside in Northern Europe. The results suggest an interaction between cultural background and current institutions, where building trust in Northern Europe is a long process but the adjustment to the trust levels in Southern and Eastern Europe is fast.
Keywords: D13; D83; J62; Z13; 330; Intergenerational transmission; Trust; Immigrants; Cultural transmission; Integration of immigrants; Soziale Integration; Generationengerechtigkeit; Migranten; Kulturelle Identität; Europa; Nordeuropa